2022
DOI: 10.12659/ajcr.935451
|View full text |Cite
|
Sign up to set email alerts
|

A 46-Year-Old Thai Woman with Secondary Acquired Pure Red Cell Aplasia Due to Treatment with Recombinant Erythropoietin While on Dialysis for End-Stage Renal Disease Who Recovered Following ABO-Incompatible Kidney Transplantation

Abstract: Patient: Female, 46-year-old Final Diagnosis: Pure red cell aplasia (PRCA) undergoing ABO-incompatible kidney transplantation Symptoms: End-stage kidney disease (ESKD) with anemia Medication:— Clinical Procedure: — Specialty: Nephrology Objective: Rare disease Background: Pure red cell aplasia (PRCA) is an uncommon cause of anemia in end-stage kidney disease (ESKD). It is attributed to recombinant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The Thai ESA registry reported that the incidence of anti-rHuEPO-induced PRCA in Thai patients was at least 1.7 per 1000 patient years 18 . This incidence is much higher than the incidence of anti-rHuEPO-induced PRCA in western countries 2 , 4 , 9 12 , 18 – 20 . Our previous data 4 and other groups 3 , 7 suggested the role of HLA-DRB1*09-DQB1*03:09 and HLA DRB1*12:02 as risk factors for anti-rHuEPO-induced PRCA.…”
Section: Introductionmentioning
confidence: 70%
“…The Thai ESA registry reported that the incidence of anti-rHuEPO-induced PRCA in Thai patients was at least 1.7 per 1000 patient years 18 . This incidence is much higher than the incidence of anti-rHuEPO-induced PRCA in western countries 2 , 4 , 9 12 , 18 – 20 . Our previous data 4 and other groups 3 , 7 suggested the role of HLA-DRB1*09-DQB1*03:09 and HLA DRB1*12:02 as risk factors for anti-rHuEPO-induced PRCA.…”
Section: Introductionmentioning
confidence: 70%
“…A retrospective study collected anti-EPO antibody-mediated PRCA cases in French and German from 1998 to 2003, which found that there were 6 cases in total and they all got recovered one month after undergoing kidney transplant ( 6 ). We also reviewed other case reports published afterward and found that 6 (85.7%) out of 7 ESRD cases with anti-EPO antibody-mediated PRCA got recovered with Hb levels above 100 g/L within 3 months after kidney transplantation ( 12 15 ). Only one case reported partial recovery at 28 months after transplantation with persistent anti-EPO antibodies but independent of blood transfusion ( 13 ).…”
Section: Discussionmentioning
confidence: 91%